2022
DOI: 10.1088/1755-1315/1101/6/062026
|View full text |Cite
|
Sign up to set email alerts
|

Design for Circularity: The Case of the Building Construction Industry

Abstract: The role of design in transitioning towards a circular economy (CE) is strategic in the building construction industry as the potential for creating, developing, and sustaining circular value throughout the whole building life cycle is largely determined by the building design. Circular building design approaches that are being commonly deployed are often based on technical perspectives that assume buildings to be static products of the building construction industry. However, buildings are complex and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is accomplished by employing various strategies such as modular design, design for deconstruction and disassembly, design for flexibility and adaptation, design for excellence, whole systems design, design in layers, and design for reuse (Çimen, 2021;Ezeudu & Ezeudu, 2019) among other techniques. Most of the previous CE research conducted in the NBI has centered on life-cycle assessment, endof-life, materials, and waste valorization, with little emphasis placed on the significance of the design stage (Osobajo et al, 2020), which has been identified as the most effective stage for implementing CE (Dewagoda et al, 2022). Nevertheless, there are significant benefits to be gained from adopting CD in building development, particularly in addressing environmental degradation, affordability challenges, and resource scarcity.…”
Section: Adoption Of Circular Design Strategies: Salient Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is accomplished by employing various strategies such as modular design, design for deconstruction and disassembly, design for flexibility and adaptation, design for excellence, whole systems design, design in layers, and design for reuse (Çimen, 2021;Ezeudu & Ezeudu, 2019) among other techniques. Most of the previous CE research conducted in the NBI has centered on life-cycle assessment, endof-life, materials, and waste valorization, with little emphasis placed on the significance of the design stage (Osobajo et al, 2020), which has been identified as the most effective stage for implementing CE (Dewagoda et al, 2022). Nevertheless, there are significant benefits to be gained from adopting CD in building development, particularly in addressing environmental degradation, affordability challenges, and resource scarcity.…”
Section: Adoption Of Circular Design Strategies: Salient Benefitsmentioning
confidence: 99%
“…The emergence of CE in the AECO industry has influenced various stages of the building procurement process (Çimen, 2021;Ellen MacArthur Foundation [EMF], 2017; Ezeudu & Ezeudu, 2019;Mboli et al, 2020), particularly in the design stage (Al-Hamrani et al, 2021;Kayacetin et al, 2022). The design stage has been identified as the most efficient and effective phase of sustainable construction for implementing CE strategies (Dewagoda et al, 2022). Circular design strategies have made it feasible to integrate CE into the design stage, providing a range of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies have identified CEBM in the construction context, and none of these studies have properly defined or elaborated on the practical applicability of the model. Further, considering the value chain context, Dewagoda et al [36] adopted Porter's value chain (PVC) concept to create a "design for circularity" approach to establish and maintain circular value throughout the entire building lifecycle. Drawing inspiration from PVC, Ding et al [37] established a circular value chain framework for construction and demolition waste recycling enterprises to analyse internal resources and capabilities, summarise the challenges they currently face, and propose strategies for their development.…”
Section: Introductionmentioning
confidence: 99%